Examining Regional Differences of Dietary Inflammatory Index and Its Association with Depression and Depressive Symptoms in Korean Adults - Shin, Dayeon (Int J Environ Res Public Health, 2020)
The relationship between the dietary inflammatory index (DII(®)) and depression and depressive symptoms in South Korean adults remains unclear. This study aimed to examine the overall relationship between the DII and depression in South Korea and to evaluate the association between the DII and depressive symptoms and depression across regions among Korean adults aged ≥19 years. A total of 15,929 study participants were selected from the Korea National Health and Nutrition Examination Survey (KNHANES) 2014–2017. Energy-adjusted (E-DII) scores were calculated using 24-h dietary recall data. Depression and depressive symptoms were measured on the basis of the Korean version of the Patient Health Questionnaire 9-item scale, a doctor’s diagnosis of depression, and self-reported depressive symptom-related questionnaire. Overall, 4.2% of the participants had depression, with notable gender differences (i.e., 2.4% in men and 6.2% in women). Korean adults residing in the Capital area, Chungcheong-do and Jeju-do, and with diets in the highest tertile of the E-DII (most pro-inflammatory diet) had significantly increased odds of having depression and depressive symptoms compared with those in the lowest tertile of the E-DII (most anti-inflammatory diet) after controlling for covariates (adjusted odds ratio (AOR): 1.44, 95% confidence interval (CI): 1.04–1.99; AOR 2.97, 95% CI 1.36–6.52; AOR 4.06, 95% CI 1.56–10.53, respectively). No association between the E-DII and depression/depressive symptoms was found in other regions of South Korea. A pro-inflammatory diet is associated with greater odds of depression and depressive symptoms, with distinct regional differences. The present study provides evidence regarding existing regional differences in the association of the E-DII with depression and depressive symptoms.